Micromachined inertial switch for sub‐g monitoring using gravity‐based threshold compensation - Rui You (Wiley, 2021)
Abstract This letter presents the original design of a microelectromechanical systems inertial switch with ultra‐low threshold (∼0.6 g) and great potential for batch manufacturing. The gravity is utilized to narrow the gap between electrodes during operation, defined here as threshold compensation. This lightens the fabrication burden, enabling the device to be made by standard silicon‐on‐glass micromachining without excessive optimization. Finite element analysis has been conducted to demonstrate positive effects of gravity involvement (9.4 μm reduction of the gap) and compliance design of the movable electrodes (multiplied contact time and less than half coefficient of restitution). Fabricated inertial switches have been installed into a vibration system to test fundamental characteristics. Under vibration conditions with amplitude of 0.6 g and frequencies from 25 to 40 Hz, the devices achieve reliable switching with triggering time ranging from 81.2 to 119.3 μs.